Development of Synergy-Based Combination for Learning and Memory Using in vitro, in vivo and TLC-MS-Bioautographic Studies - Khan, Maaz Ahmed; Srivastava, Varsha; Kabir, Mariya; Samal, Monalisha; Insaf, Areeba; Ibrahim, Mohammad; Zahiruddin, Sultan; Ahmad, Sayeed (Frontiers in Pharmacology, 2021)
The present study is aimed at developing a synergistic combination to enhance learning and memory in Alzheimer’s patients with the help of eight common medicinal plants used in the AYUSH system. Aqueous and hydroalcoholic extracts of eight medicinal plants from the AYUSH system of medicine were prepared. These were subjected to in vitro anticholinesterase activity, to find out the combination index of synergistic combination. The synergistic combination and their individual extracts were subjected to total phenol, flavonoid and antioxidant activity estimation. Further, in vivo neurobehavioral studies in rats were carried out followed by TLC-MS-bioautographic identification of bioactive metabolites. Out of the sixteen extracts, aqueous extracts of Withania somnifera (WSA) and Myristica fragrans (MFA) were selected for the development of synergistic combination based on their IC50 value in in vitro anticholinesterase assay. The synergistic combination inhibited the anticholinesterase activity significantly as compared to the individual extracts of WSA and MFA. The synergistic combination also showed more phenolic and flavonoid contents with potential antioxidant activity. The TLC-bioautography showed four white spots in WSA, signifying sitoindosides VII, VIII, quercetin, isopelletierine and Withanolide S as AChE inhibitory compounds while showing five white spots of anti-cholinesterase active metabolites identified as eugenol, methyl eugenol, myristic acid, galbacin and β-sitosterol in MFA. The observation of neurocognitive behavior in amnesia induced subjects manifested that both the synergistic combinations showed comparable results to that of standard piracetam, though the synergistic combination containing a higher concentration of WSA showed more appreciable results in ameliorating dementia in rats. The study suggests that the synergy based combination successfully enhanced memory and learning by abating free radical and acetylcholine levels, and increased learning and memory in rats, providing a strong rationale for its use in the treatment of dementia and Alzheimer’s disease.